Jazz improvisation: Achieving a high aesthetic level during vocal education (Música Hodie, 2025)
Jazz vocal improvisation remains insufficiently studied in pedagogical contexts, despite its central role in the aesthetic outcomes of performance. This study investigated parametric correlations between improvisational components and aesthetic achievements within cross-cultural contexts of vocal education. Employing mixed-method triangulation (n=197 conservatory students; 57.8% Chinese, 42.2% Western origin), the study implemented structured pedagogical interventions over twelve months. Quantitative assessment utilized validated rating scales (AJVA, α=.91) and hierarchical statistical procedures, while qualitative measurements captured phenomenographic categorizations of experiential descriptions. Hierarchical evaluation demonstrated the primacy of “artistic idea” (weight 2.27; 95% CI: 2.14–2.40), followed by “intonational variability” (weight 2.19; 95% CI: 2.05–2.33). Factor analysis confirmed a technical-expressive duality (cumulative variance=88.2%). Longitudinal tracking revealed logarithmic skill progression: harmonic sophistication increased by 169.4%; timbral diversification expanded register distribution from mid-range dominance (83.7%) to balanced chest, head, and mixed register usage; phonetic modifications enlarged syllabic inventory from 7.3 to 24.7 discrete units. Metacognitive verification showed systematic perceptual convergence (Cohen’s d decreased from 1.076 to 0.104; inter-rater reliability improved from ICC=0.68 to 0.87). The findings advocate pedagogical restructuring. First, instructional interventions should be sequenced according to documented developmental trajectories. Second, it is necessary to implement weighted assessment protocols reflecting parametric prioritization. Additionally, pedagogical strategies should incorporate self-evaluative convergence strategies. Furthermore, vocal training frameworks must expand beyond traditional technical-expressive dichotomies by embracing cross-cultural aesthetic principles. Together, these adjustments would contribute to the development of empirically grounded methodologies in jazz vocal education.